AMERICA IN THE SHADOW OF 2016 PRESIDENTIAL ELECTIONS AND RISE OF THE REPUBLICANS - Aghazada, Nihal; Yildiz, Kadir (European Scientific Journal, ESJ, 2015)
Democrats and Republicans have been occupying the major part of the presidential elections in America with strong competences throughout the history. The article particularly focuses on the recent elections referring to 2016, presidential elections. In spite of some supports given to Obama due to his implemented policies such as immigration policy, the latest midterm elections substantiated the shifts in decisions of Americans. Furthermore, internal and external failures impeding President Obama and pushing him into some foreign policy changes. The article puts a couple of argumentation between Democrats and Republicans to show who possesses the preponderance for 2016.